PENGEMBANGAN MEDIA PERMAINAN TAPAK GUNUNG BERBASIS PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PPKN SEKOLAH DASAR - Waryuni Nurmiati; Nina Nurhasanah; Andi Ali Saladin (Universitas Trilogi, 2021)
This research and development aim to produce a learning media through character education-based on Tapak Gunung games and specifically introducing character values in Strengthening Character Education in elementary schools. This study is a Research and Development (R & D). The method of this study using the ADDIE development model. The subjects of this study were the teacher of grade IV Elementary School Private Laboratory, Elementary School Teacher Education, State University Jakarta, grade II and IV students of elementary school in total were 24 subjects. Sources of data obtained through interviews and questionnaires, which are then processed using qualitative and quantitative analysis techniques. The results of the validation of this studyobtained an average value of 95% by material experts, 97.05% by media experts, and 96.43% by linguists. Based on student trials, it was obtained an average score of 94.68% for one-to-one, 93.88% for the small group, and 94.16% for the field test. In addition, the media assessment by the teacher obtained a score of 98.21%. The results of this study indicate that the character education-based tapak gunung game media is in a very good category, so it is suitable for use on civic-education learning in elementary schools.